A five year financial plan for Business Machines Corporation (BISMAC) - Olea, Almari S. 4 0 16; 5 (2016)
EXECUTIVE SUMNMARY: BISMAC or Business Machines Corporation has grown into the largest integrated office and bank equipment distributor in the Philippines. It has established a reputation for high quality office machines and prides itself in being an authorized service center for big companies such as BROTHER, CANON and EPSON. (www.bismac.com.ph,2015) The entity has 5 wholly-owned branches in Cebu, Iloilo, Bacolod, Davao and Cagayan de Oro. It has established a reputation for high quality office machines and reliable after sales support. However, analysing the entity's financial statements for the last 5 years, the proponents found out that the entity is having problem regarding its profitability due to high cost of sales and operating expenses which leads to inadequate current fund to cover liabilities insufficient net profit margin and slow turnover period. With such problems, the proponents came up an alternative to strengthen supplier relationship and resource to local sourcing in which it will reduce the cost, increase revenue, accelerate turnover period and improve cash flow. This alternative will lead to generous terms, timely delivery of quality materials, customer satisfaction, access to latest innovations and can also saves the entity's money. Moreover, the entity will have access to mutually beneficial transactions and arrangement for payments.
Financial Plan : (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2